2019
DOI: 10.1177/2164956119858034
|View full text |Cite
|
Sign up to set email alerts
|

Nonpharmacological Self-Management of Migraine Across Social Locations: An Equity-Oriented, Qualitative Analysis

Abstract: Background: Migraine is a disabling neurological disorder and the sixth biggest cause of disability worldwide. The World Health Organization has declared migraine a major public health problem due to a paucity of knowledge about cause and effective treatment options. Both in incidence and severity, migraine disproportionately affects people occupying marginalized social locations (SL). Managed pharmacologically, migraine is treated with daily preventive and as-needed abortive medications. Both come with high l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…30,32 In both studies that report on finding preferences for SDM, patients reported a need for information from clinicians about migraine as a condition as well as about treatment options. 26,30 In one of these studies, patients reported the absence of SDM where insurance or health system changes excluded them from clinicians or treatments they may have worked to find (quote 1.20). 31 In other study, patients reported absence of SDM where they perceived low or lack of provider knowledge about migraine (quote 1.21).…”
Section: Tailored Approachmentioning
confidence: 99%
See 3 more Smart Citations
“…30,32 In both studies that report on finding preferences for SDM, patients reported a need for information from clinicians about migraine as a condition as well as about treatment options. 26,30 In one of these studies, patients reported the absence of SDM where insurance or health system changes excluded them from clinicians or treatments they may have worked to find (quote 1.20). 31 In other study, patients reported absence of SDM where they perceived low or lack of provider knowledge about migraine (quote 1.21).…”
Section: Tailored Approachmentioning
confidence: 99%
“…29 In some studies of medications, where non-pharmacologic treatment options were not selected, patients acknowledged their need for medication along with expressing a desire to use less medication or find non-drug treatment options. 26 In one study of non-pharmacologic treatment for migraine, all study participants took some sort of medication for migraine. They acknowledged the need for this, but repeatedly expressed a desire to use non-pharmacological approaches for prevention, long-term migraine reduction, and contributions to overall health (quote 2.4).…”
Section: Details Of Themes Identified Regarding Preferences About The...mentioning
confidence: 99%
See 2 more Smart Citations
“…Although medications are often used as first-line treatments for migraine, some patients experience intolerable side effects and may have increased risk for migraine chronification (1,2). As a result, individuals with migraine often express interest in holistic or integrative approaches over medication alone as part of a long-term management strategy (3). Integrative treatment approaches that address pathophysiologic processes involved in migraine attacks and/or reduce migraine symptoms have potential to reduce migraine frequency and severity.…”
Section: Introductionmentioning
confidence: 99%